THE IMPORTANCE OF THE ROLE OF THE TEACHER IN THE ARTIS-TIC AND AESTHETIC DEVELOPMENT OF PRESCHOOL CHILDREN ACCORDING TO THE PROGRAM "WORLD OF WIZARDS" - Chabrova T. L. (Modern American Journals, 2025)
In the article, the author reveals the role of the educator in artistic and aesthetic development, how it influences the formation of children's aesthetic attitude to the environment: development of the ability to see and feel beauty in nature, actions, art, to understand the beautiful; education of artistic taste, the need to know the beautiful through the author's program "World of Wizards".
Keywords: Artistic and aesthetic development, visual activity, educator, preschool age, program, integration method, kindergarten.